Consumer-Based Sensory Profiling of Commercial Cascara Products Using Check-All-That-Apply (CATA): Key Attributes and Preference Segmentation - Dita Yuliarti; Hadi Munarko; Luqman Agung Wicaksono; Ajeng Astrini Brahmanti; Tsania Rizqiya Rahawarin (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Cascara, a coffee husk by-product of coffee processing, has recently gained attention as a refreshing beverage. This study aimed to characterize the sensory profiles of commercial cascara products derived from different post-harvest processing methods using Check-All-That-Apply (CATA), to identify key sensory attributes driving consumer perception, and to segment consumer preferences based on sensory responses. Five commercial cascara products were evaluated, namely natural Arabica cascara, natural Robusta cascara, fully washed Arabica cascara, honey-processed Arabica cascara, and wine-processed Arabica cascara. The results revealed that cascara brews exhibited distinct sensory profiles, significantly influenced by coffee variety and post-harvest processing methods (p < 0.05). Lemon flavor, dried fruit aroma and flavor, and fermented aroma were identified as the main drivers of liking, whereas bitterness negatively affected consumer preference. Naturally processed cascara Arabica was most preferred among panelists, and preference was significantly influenced by gender. These findings provide new insights into the development of cascara-based beverages as refreshing drinks Contribution to Sustainable Development Goals (SDGs):SDG 3: Good health and well-beingSDG 8: Decent work and economic growthSDG 12: Responsible consumption and production